Bidirectional Synaptic Plasticity Is Driven by Sex Neurosteroids Targeting Estrogen and Androgen Receptors in Hippocampal CA1 Pyramidal Neurons - Tozzi, Alessandro; Durante, Valentina; Manca, Paolo; Di Mauro, Michela; Blasi, Juan; Grassi, Silvarosa; Calabresi, Paolo; Kawato, Suguru; Pettorossi, Vito Enrico (Frontiers in Cellular Neuroscience, 2019)
Neuroactive estrogenic and androgenic steroids influence synaptic transmission, finely modulating synaptic plasticity in several brain regions including the hippocampus. While estrogens facilitate long-term potentiation (LTP), androgens are involved in the induction of long-term depression (LTD) and depotentiation (DP) of synaptic transmission. To examine sex neurosteroid-dependent LTP and LTD in single cells, patch-clamp recordings from hippocampal CA1 pyramidal neurons of male rats and selective antagonists for estrogen receptors (ERs) and androgen (AR) receptors were used. LTP induced by high-frequency stimulation (HFS) depended on activation of ERs since it was prevented by the ER antagonist ICI 182,780 in most of the neurons. Application of the selective antagonists for ERα (MPP) or ERβ (PHTPP) caused a reduction of the LTP amplitude, while these antagonists in combination, prevented LTP completely. LTP was never affected by blocking AR with the specific antagonist flutamide. Conversely, LTD and DP, elicited by low-frequency stimulation (LFS), were impeded by flutamide, but not by ICI 182,780, in most neurons. In few cells, LTD was even reverted to LTP by flutamide. Moreover, the combined application of both ER and AR antagonists completely prevented both LTP and LTD/DP in the same neuron. The current study demonstrates that the activation of ERs is necessary for inducing LTP in hippocampal pyramidal neurons, whereas the activation of ARs is required for LTD and DP. Moreover, both estrogen- and androgen-dependent LTP and LTD can be expressed in the same pyramidal neurons, suggesting that the activation of sex neurosteroids signaling pathways is responsible for bidirectional synaptic plasticity.